(untitled) (Comprehensive Journal of Science, 2025)
This study investigates the prepositions in Surah Taha, aiming to elucidate their role in guiding semantic interpretation and ensuring the coherence of the Qur’anic text. Employing a descriptive-analytical methodology, the study reveals several significant findings, foremost among them the diversity of the prepositions’ semantic functions. These prepositions are not merely connective tools; rather, they perform a clear semantic role within the Qur’anic discourse, actively contributing to meaning construction, defining semantic relationships among words and structures, and clarifying the Qur’anic objectives alongside the educational and ethical meanings embedded in Surah Taha.